Network pattern and risk characteristics of global cobalt material trade from the perspective of industry chain - Haoran, LI; Wenjie, XU; Qiang, JI; Xiaolei, SUN (Zi yuan ke xue, 2025)
[Objective] Cobalt, as a key strategic resource, shows a pronounced geographical separation between supply and demand, with growing concerns over trade security. Systematically identifying cobalt trade patterns and their evolving risks is crucial for maintaining the stability of industry chains and optimizing resource security policies. [Methods] Focusing on cobalt material trade, this study selected 29 cobalt products across four stages of the industry chain—mining, production, manufacturing, and waste management—to construct a global cobalt material trade network. Based on the network topology from 2012 to 2022, trade risk indices for the global cobalt material trade network are developed from three dimensions: import concentration, resource acquisition difficulty, and trade intermediation. [Results] (1) The geographical distribution of cobalt material trade patterns showed a core clustering trend. The heterogeneity in the mining and manufacturing stages weakened, while that in the production stage increased, with no significant evolutionary trend observed in the waste management stage. (2) The trade risks of major importing countries (regions) constrained the stability of the global cobalt trade network. Although high-risk countries (regions) have improved their intermediary control and resource acquisition capabilities, import concentration remained the dominant factor influencing trade risks. (3) Trade dependency relationships among countries (regions) differed significantly across the mining, production, manufacturing, and waste management stages, and the driving forces influencing these dependencies varied as well. In the mining stage, dependencies were primarily concentrated in Asia and Africa. In the production stage, trade dependencies began to spread globally. In the manufacturing stage, dependencies among Asian countries strengthened significantly. In the waste management stage, trade dependencies between North American and European countries were notably close. [Conclusion] The stability of the global cobalt material trade network depends on major importing countries (regions). As a major importer, China should strengthen the diversification of its cobalt source supply, promote technological innovation and industrial upgrading, accelerate the development of waste resource recycling systems, and improve risk warning and response mechanisms to ensure supply chain security, consolidate its strategic position, and gain initiative in recycling.